#TITLE_ALTERNATIVE# - AHMAD KAUTSAR DJUNAEDY - Nim: 10614049, HANIF
Nitrogen is an important component in many biological molecules. In oil palms, the growth of fruit bunches and the capacity for photosynthesis is dependant on its nitrogen uptake. Soil microbes in and around the plants’ roots play an important role in maintaining adequate nitrogen balance by regulating key nitrogen cycle processes, including nitrification, denitrification, and nitrogen fixation. The purpose of this study is to detect and quantify the bacteria that regulate these processes, mainly ammonia-oxidizing bacteria (AOB), nitrite-oxidizing bacteria (NOB), heterotrophic denitrifiers (DEN), and nitrogen fixing bacteria (BNF), in the rhizosphere and non-rhizosphere soils of twelve plots in PT. Astra Agro Lestari’s oil palm plantation, as well as determining the environmental variables that correlate with their growth. This was done by targeting and amplifying the amoA, nxrB, nosZ , and nifH genes of AOB, NOB, DEN, and BNF respectively from isolated DNA samples using the PCR and Real-Time PCR System. On average, the BDS samples have higher abundances from all four genes while the P3T2 samples have the lowest. However, ANOVA shows that the only significant difference was with the nifH gene abundance, with the samples from BDS and P2T2 having seven times higher the gene abundance compared to samples from P1T2 and P3T2. Comparison of rhizosphere and non-rhizosphere soils showed no significant difference in gene abundance, however, the rhizosphere samples of P1T2 and P3T2 have higher evenness than the non-rhizosphere samples while for the P2T2 and BDS it’s the opposite. Further correlation analysis shows that amoA and nifH gene abundance are significantly correlated, along with the nosZ and nifH gene abundance in the rhizosphere. Correlation and multivariate analysis showed that sand concentration, total cation, available phosphate, and C/N ratio exerted a significant effect on amoA, nxrB, nosZ , and nifH gene abundances respectively and explains the variation in gene abundance.